Efficacy and safety of canagliflozin monotherapy in subjects with type 2 diabetes mellitus inadequately controlled with diet and exercise. Issue 4 (24th January 2013) - Stenlöf, K.; Cefalu, W. T.; Kim, K.‐A.; Alba, M.; Usiskin, K.; Tong, C.; Canovatchel, W.; Meininger, G.
<x xml:space="preserve">Abstract</x> Aims Canagliflozin is a sodium glucose co‐transporter 2 inhibitor in development for type 2 diabetes mellitus (T2DM). The efficacy and safety of canagliflozin were evaluated in subjects with T2DM inadequately controlled with diet and exercise. Methods In this 26‐week, randomized, double‐blind, placebo‐controlled, phase 3 trial, subjects (N = 584) received canagliflozin 100 or 300 mg or placebo once daily. Primary endpoint was the change from baseline in haemoglobin A1c (HbA1c) at week 26. Secondary endpoints included the proportion of subjects achieving HbA1c < 7.0%; change from baseline in fasting plasma glucose (FPG), 2‐h postprandial glucose (PPG) and systolic blood pressure (BP); and percent change in body weight, high‐density lipoprotein cholesterol (HDL‐C) and triglycerides. Adverse events (AEs) were recorded throughout the study. Results At week 26, HbA1c was significantly reduced from baseline with canagliflozin 100 and 300 mg compared with placebo (−0.77, −1.03 and 0.14%, respectively; p < 0.001 for both). Both canagliflozin doses significantly decreased FPG, 2‐h PPG, body weight and systolic BP (p < 0.001 for all), and increased HDL‐C compared with placebo (p < 0.01 for both). Overall incidences of AEs were modestly higher with canagliflozin versus placebo; rates of serious AEs and AE‐related discontinuations were low and similar across groups. Incidences of genital mycotic infections, urinary tract infections and osmotic diuresis‐related AEs were higher with canagliflozin; these led to few discontinuations. The incidence of hypoglycaemia was low across groups. Conclusion Canagliflozin treatment improved glycaemic control, reduced body weight and was generally well tolerated in subjects with T2DM inadequately controlled with diet and exercise.